Genitourinary Syndrome of Menopause: Epidemiology, Physiopathology, Clinical Manifestation and Diagnostic - Sarmento, Ayane Cristine Alves; Costa, Ana Paula Ferreira; Vieira-Baptista, Pedro; Giraldo, Paulo César; Eleutério, José; Gonçalves, Ana Katherine (Frontiers in Reproductive Health, 2021)
Genitourinary syndrome of menopause (GSM) is a term used to define a compilation of signs and symptoms arising from decreased estrogenic stimulation of the vulvovaginal and lower urinary tract. GSM affects approximately 27% to 84% of postmenopausal women and can significantly impair health, sexual function, and quality of life. The main signs and symptoms include, among others, vulvovaginal dryness, burning, irritation, dyspareunia, urinary symptoms of urgency, dysuria, or recurrent urinary tract infection. The diagnosis can be made through anamnesis, questionnaires, physical exams, and, sometimes, complementary exams. Objective vaginal assessment is essential and can be complemented by using the Vaginal Health Index (VHI), Vaginal Maturation Index (VMI), or vaginal pH measurement. The acknowledgment of this condition by health professionals is crucial for its identification and proper management and exclusion of other conditions that make a differential diagnosis with it.